Unlocking the mechanisms of change in the MAMAACT intervention to reduce ethnic disparity in stillbirth and newborns' health: integration of evaluation findings - Villadsen, Sarah Fredsted; Johnsen, Helle; Damsted Rasmussen, Trine; Ekstrøm, Claus Thorn; Sørensen, Janne; Azria, Elie; Rich-Edwards, Janet; Essén, Birgitta; Christensen, Ulla; Smith Jervelund, Signe; Nybo Andersen, Anne-Marie (Frontiers in Health Services, 2024)
Ethnic disparities in stillbirth exist in Europe and suboptimal care due to miscommunication is one contributing cause. The MAMAACT intervention aimed to reduce ethnic disparity in stillbirth and newborns' health through improved management of pregnancy complications. The intervention encompassed training of antenatal care midwives in cultural competencies and intercultural communication combined with health education materials for the expecting parents about symptoms of pregnancy complications. The evaluation consisted of a qualitative in-depth implementation analysis and a process evaluation embedded in a cluster randomized trial including 19 of 20 maternity wards in Denmark. In this article, the findings from the different evaluation perspectives are integrated. The integration follows the principles of realist evaluation by analyzing to what extent the MAMAACT activities were generating mechanisms of change in interaction with the context. The integration analysis shows that the health education materials in the MAMAACT intervention contributed to heightened health literacy concerning pregnancy complications among pregnant women. Additionally, the training of midwives in cultural competency and intercultural communication raised awareness among midwives. Nonetheless, the exclusive emphasis on midwives and the inflexibility in care provision hindered them from changing their communication practices. To enhance the cultural competence in maternity care, it is essential to implement more comprehensive initiatives involving healthcare professionals in maternity care at all levels, from pregraduate to postgraduate. Adequate interpreter services and management support should also be ensured. Currently, the Danish antenatal care system faces challenges including inadequate information transfer between healthcare sectors, insufficient differentiation of care, and inflexibility in midwife scheduling. This results in a lack of responsiveness to the individual needs of women with immigrant backgrounds, potentially reproducing health inequities.